Epigenetic changes during sepsis: on your marks!. Issue 1 (December 2015) - Bataille, Aurélien; Galichon, Pierre; Ziliotis, Marie-Julia; Sadia, Iman; Hertig, Alexandre
Abstract Epigenetics is the study of how cells, organs, and even individuals utilize their genes over specific periods of time, and under specific environmental constraints. Very importantly, epigenetics is now expanding into the field of medicine and hence should provide new information for the development of drugs. Bomsztyk and colleagues have detected major epigenetic changes occurring in several organs as early as 6 h after the onset of a mouse model of multiple organ dysfunction syndrome induced byStaphylococcus aureus lung injury. Decrease in mRNA of key genes involved in endothelial function was found to be associated with (and potentially explained by) a decrease in permissive histone marks, while repressive marks were unchanged. We discuss here the limitations of a whole-organ as opposed to a cell-specific approach, the nature of the controls that were chosen, and the pitfalls of histone modifications as a cause of the eventual phenotype. While the use of 'epidrugs' is definitely welcome in the clinic, how and when they will be used in sepsis-related multiple organ dysfunction will require further experimental studies.